ANALISIS RISIKO PRODUKSI WORTEL DAN BAWANG DAUN DI KAWASAN AGROPOLITAN CIANJUR JAWA BARAT - Jamilah, Mila; Nurhayati, Popong (Forum Agribisnis, 2011)
One of horticultural commodities which contribute significantly to Gross Domestic Product (GDP) is vegetables. Agropolitan Cianjur is one vegetable producing areas in Indonesia with the priority commodity of carrots and leeks. Farmers in the area of Cianjur agropolitan face the constraints in production fluctuations from the two commodities which indicate a production risk. Therefore, we need to analyze the production risk of carrot and leek  in the region of Cianjur agropolitan andto  analyze the alternative of risk management handlin gin  the production of carrot and leek that can be applied in the region of Cianjur agropolitan. The method used to analyze the level of production risk in carrots and leeks is variance, standard deviation, and coefficient variation That tools can find the alternative production of risk management. Base on the return of productivity, production risk of carrots is 26 percent and lees is 29 percent. The Alternative of risk management is, first, farmers should irrigate carrot and leeks in the dry season and use plastic mulch for leeks. Second, farmers should implement the Integrated Pest Management (IPM). Third, farmers must do proper fertilization and rotate the cropping pattern well. Fourth, farmers must use appropriate input variables according to the Standard Operating Procedure (SOP). Fifth, the government must improve training and extension in cultivation of carrots and leeks and also increase the oversight of the farmers performance. Sixth, diversification by intercropping.